2018
DOI: 10.1016/j.tvjl.2018.10.008
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of ultrasonic pachymetry and Fourier-domain optical coherence tomography for measurement of corneal thickness in dogs with and without corneal disease

Abstract: Several ultrasonic and Fourier-domain optical coherence tomography (FD-OCT) pachymeters are used to measure corneal thickness in canine patients and research subjects. This study assessed the reliability of and consistency between two ultrasonic pachymetry (USP) devices, Pachette 3 and Accupach VI, as well as automated and manual measurements obtained using FD-OCT in dogs with and without corneal disease. Corneal thickness measurements were compiled from 108 dogs and analyzed using mixed effects linear regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Positive correlation exists between endothelial cell function and Central corneal thickness (CCT) 5 . Central corneal thickness can be measured by ultrasonic pachymeter 6 . Ultrasonic pachymeters allow surgeons to measure the thickness of the cornea in patients suffering from glaucoma, hypertension or those who are considered for refractive surgery without causing damage to this sensitive organ.…”
Section: Introductionmentioning
confidence: 99%
“…Positive correlation exists between endothelial cell function and Central corneal thickness (CCT) 5 . Central corneal thickness can be measured by ultrasonic pachymeter 6 . Ultrasonic pachymeters allow surgeons to measure the thickness of the cornea in patients suffering from glaucoma, hypertension or those who are considered for refractive surgery without causing damage to this sensitive organ.…”
Section: Introductionmentioning
confidence: 99%
“…8 The cornea may become thicker in dogs than in humans because of the less intertwined collagen in the corneal stroma and the absent Bowman's layer. 21,35 Additionally, the classification of clinical cell grade used in this study was not detailed, and the lack of direct comparison with cells appearing on OCT and slit-lamp biomicroscopy are also limitations of this study. Aqueous flare and cell grading by two examiners could also be a limitation in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Second, the eyes with a corneal thickness of less than 800 μm were included for a better scan quality of the anterior chamber. A previous study also suggested that the use of SD‐OCT in dogs was appropriate when the corneal thickness was less than 800 μm 21 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations